DBSCAN CLUSTERING ALGORITHM ON HADOOP ENVIRONMENT - Krishan Mohan Pate, Anubha, Garima Jain (International Journal of Advanced Science and Technology, 2020)
Now-a-days millions and millions of data are being generated from various sources such as social networking sites, web, multimedia (audio, video, and images), etc. Hence the term BIG DATA has emerged to deal with the immense amount of data. To analyze, process massive amount of data and to extract meaningful information is a very challenging task. Various technologies i.e. parallel, map reduce are used which entail massive amount of data. This paper analyses DBSCAN clustering design which is exemplified under MapReduce parallel registering system, by a HDFS distributed stockpiling and MapReduce circulated figuring, which utilize the benefits of Hadoop in managing large information and significantly improves the proficiency of the calculation. This Algorithm discover bunches in discretionary shapes, size, and just as channel out outlier. In this paper different DBSCAN Algorithms is compared in terms of execution time and number of clusters and it is noted that IDBSCAN Algorithms is better.